POCl3 Mediated Syntheses, Pharmacological Evaluation and Molecular Docking Studies of Some Novel Benzofused Thiazole Derivatives as a Potential Antioxidant and Anti-inflammatory Agents - Raut, Dattatraya G.; Patil, Sandeep B.; Choudhari, Prafulla B.; Kadu, Vikas D.; Lawand, Anjana S.; Hublikar, Mahesh G.; Bhosale, Raghunath B. (Current Chemical Biology, 2020)
Background: The present research work is focused on the development of alternative antioxidant and anti-inflammatory agents. The review of the literature reveals that many benzofused thiazole analogues have been used as lead molecules for the design and development of therapeutic agent, including anticancer, anti-inflammatory, antioxidant and antiviral. The synthesized benzofused thiazole derivatives are evaluated for in vitro antioxidant, anti-inflammatory activities and molecular docking study. Thus, the present research work aims to synthesize benzofused thiazole derivatives and to test their antioxidant and antiinflammatory activities. Objective: To design and synthesize an alternative antioxidant and anti-inflammatory agents. Methods: The substituted benzofused thiazoles 3a-g were prepared by cyclocondensation reaction of appropriate carboxylic acid with 2-aminothiophenol in POCl3 and heated for about 2-3 h to offer benzofused thiazole derivatives 3a-g. All the newly synthesized compounds were in vitro screened for their anti-inflammatory and antioxidant activities by using a known literature method. Results: At the outset, the study of in vitro indicated that the compounds code 3c, 3d and 3e possessed distinct anti-inflammatory activity as compared to a standard reference. All the tested compounds show potential antioxidant activity against one or more reactive (H2O2, DPPH, SO and NO) radical scavenging species. Additionally, docking simulation is further performed to the position of compounds 3d & 3e into the anti-inflammatory active site to determine the probable binding model. Conclusion: New anti-inflammatory and antioxidant agents were needed; it has been proved that benzofused thiazole derivatives were 3c, 3d and 3e constituted as an interesting template for the evaluation of new anti-inflammatory agents and an antioxidant’s work also may provide an interesting template for further development.
Keywords: benzofused thiazoles